Facial alveolar bone alterations and gray value changes based on cone beam computed tomography around maxillary anterior implants: A clinical retrospective study of 1–3 years. Issue 5 (12th February 2020) - Zhou, Yi; Gao, Jiayu; Sheng, Min; Qi, Wenting; Jin, Jiali; He, Fuming
Abstract: Objectives: The purpose of this cone beam computed tomography (CBCT) study was to describe facial alveolar bone alterations and gray value (GV) changes around implants in aesthetic anterior maxilla with simultaneous guided bone regeneration (GBR) and to investigate potential influence of factors related to vertical alveolar bone stability, such as particle sizes of the deproteinized bovine bone mineral (DBBM) used. Materials and Methods: A retrospective study design was adopted. Four facio‐palatal cross‐sectional CBCT images of 166 implants from 124 patients who had maxillary anterior implants were obtained. Measurements of the vertical facial alveolar bone level (VFBL), horizontal facial alveolar bone thickness (HFBT), and GV were identified of 1–3 years. Then, correlation coefficients for those parameters were calculated. Finally, linear mixed models were established to investigate potential factors influencing vertical alveolar bone resorption. Results: Facial alveolar bone underwent fast bone modeling and remodeling during the first 6 months, with decreases of 1.00 ± 1.19 and 0.74 ± 0.86 mm in VFBL and HFBT in implant shoulder, respectively, and there was positive and significant correlation between the alterations in VFBL and HFBT1 ( r s = .516, p = .000). Linear mixed models identified particle size of DBBM as a critical factor associated with vertical bone resorption ( p = .000). The GV gradually increased during the follow‐up period. Conclusions: Rapid and unavoidable peri‐implant bone resorption usually happened during the first 6 months after implant placement. GBR is a predictable treatment for maxillary anterior implants, since GV has an increasing trend. Large bone particles of DBBM help maintain vertical alveolar bone stability.